Novel Contributors and Mechanisms of Cellular Senescence in Hypertension-Associated Premature Vascular Aging. (15th April 2019) - McCarthy, Cameron G; Wenceslau, Camilla F; Webb, R Clinton; Joe, Bina
Abstract: Hypertension has been described as a condition of premature vascular aging, relative to actual chronological age. In fact, many factors that contribute to the deterioration of vascular function as we age are accelerated in hypertension. Nonetheless, the precise mechanisms that underlie the aged phenotype of arteries from hypertensive patients and animals remain elusive. Cellular senescence is an age-related physiologic process in which cells undergo irreversible growth arrest. Although controlled senescence negatively regulates cell proliferation and promotes tissue regeneration, uncontrolled senescence can contribute to disease pathogenesis by presenting the senescence-associated secretory phenotype, in which molecules such as proinflammatory cytokines, matrix metalloproteases, and reactive oxygen species are released into tissue microenvironments. This review will address and critically evaluate the current literature on the role of cellular senescence in hypertension, with particular emphasis on cells types that mediate and modulate vascular function and structure.